New records of vascular plants for the department of Boyacá, Colombia - Gómez-Parra, Sofía; Mendoza-Cifuentes, Humberto; Morales-Puentes, María Eugenia; Malagón, María; Manrique, Naisla; Moreno, Diego (Instituto de Ecología, A.C., 2019)
Background and Aims: The páramo ecosystems have a high diversity of plant species, many of them are endemic to Colombia. However, some páramos have remained unexplored, which has generated information gaps regarding the species distribution. Therefore, the main objective of this study is to present new records of plant species for the department of Boyacá, contributing to the knowledge of the páramo flora in Rabanal.Methods: Sampling was carried out in the Rabanal Páramo area, municipality of Samacá (Loma Redonda and La Chorrera trails); species distribution was reviewed, and a brief description of the taxa that are new records for the department was made.Key results: We present novelties in the floristic diversity of the department of Boyacá. We identified eight new records of angiosperm and pteridophyte taxa, four species belong to the family Orchidaceae, two to Polypodiaceae and the remaining to Bromeliaceae and Campanulaceae, in an altitudinal range of 3200-3301 m.Conclusions: This is the first floristic approach for the northwestern sector of the Rabanal Páramo area, where eight new distribution records of plant species are recorded for the department of Boyacá. Here we highlight the significance of carrying out botanical expeditions that increase diversity knowledge, as a basis for the development of protection and conservation strategies.